Management of Cerebral Edema in Acute Liver Failure - Kok, Beverley; Karvellas, Constantine J. (Seminars in Respiratory and Critical Care Medicine, 2017)
Advances in medical care of the acute liver failure patient have led to a significant reduction in mortality related to the condition. Nevertheless, cerebral edema and ensuing brain herniation remains one of the top causes of demise in acute liver failure. Controversy remains regarding the utility of invasive intracranial pressure monitoring as well as usage of novel treatment modalities including therapeutic hypothermia. This review provides a brief summary into the pathophysiology and risk factors for developing cerebral edema in the context of acute liver failure; this review particularly provides a practical focus on general management of the patient with established cerebral edema as well as specific intracranial pressure-lowering strategies.
Keywords: acute liver failure; intracranial hypertension; cerebral edema; neuroprotection; therapeutic hypothermia